Hf‐Nd‐Sr Isotopic Composition as Fingerprint for Long‐Range Transported Eolian Dust Deposition in Glacier Snowpack of Eastern Tibetan Plateau. Issue 13 (11th July 2018) - Dong, Zhiwen; Shao, Yaping; Qin, Dahe; Kang, Shichang; Wei, Ting; Wang, Xuejia; Wang, Shijin
Abstract: This study presents the Hf‐Nd‐Sr isotopic compositions of eolian dust deposited on glacier snowpacks along a longitude transect on the eastern Tibetan Plateau, in order to trace its source areas and the provenance of long‐range transported (LRT) Asian dust on the eastern margin of Tibetan Plateau. Most of the glacier snowpack samples from northern locations (Qiyi and Lenglongling Glaciers) indicated similar Hf‐Nd‐Sr isotopic ratios with that of large central Asian deserts. However, the southern locations (Dagu, Hailuogou, and Baishui Glaciers) showed dramatic difference in the Hf‐Nd‐Sr isotopic ratios of snowpack dust compared with those of large Asian deserts, but were more similar to that of Tibetan Plateau surface crust. Hf‐Nd isotopes indicated that the southern Tibetan Plateau locations are hardly influenced by central Asian dust, but probably influenced by southward dust transport from the Loess Plateau, in addition to the arid deserts on the Tibetan Plateau surface. Meteorological data and aerosol optical depth also demonstrated the potential differences of eolian dust transport and input between the north and south locations. Loess Plateau is even in today's climate a dust sink, but dust emission from the Loess Plateau is also possible. The influence of the Tibetan Plateau and southwest vortex of China to atmospheric circulation may have caused such eolian transport, in particular for LRT eolian dust transport to southeastern Tibetan Plateau glaicers. This study is also of importance in that the Hf‐Nd isotopic fingerprinting could provide new evidences for LRT dust deposition on the Tibetan Plateau. Plain Language Summary: This study is aimed to examine the spatial variation of eolian dust transport and deposition in the eastern margin of Tibetan Plateau, for which the sources and provenance of the dust deposited in high elevation glaciers have not been investigated. The dust transport route is also important for understanding regional atmospheric circulation and climate. This study is thus intended to provide a better understanding of long‐range transported dust transport and dust deposition on the eastern margin of Tibetan Plateau. Hf‐Nd isotopic fingerprinting is used to provide new evidence for tracing long‐range transported dust in high mountain glaicers when compared with Nd‐Sr isotopes. Key Points: Snowpack samples showed marked difference of Hf, Nd, and Sr isotopic composition between north and south locations South locations Hf‐Nd‐Sr isotopes revealed dust provenance partly from the Chinese Loess Plateau Hf‐Nd isotopic fingerprinting provides new evidences for tracing LRT dust in high mountain glaicers